Advances in clinical next-generation sequencing: target enrichment and sequencing technologies. (3rd March 2016) - Ballester, Leomar Y.; Luthra, Rajyalakshmi; Kanagal-Shamanna, Rashmi; Singh, Rajesh R.
ABSTRACT: The huge parallel sequencing capabilities of next generation sequencing technologies have made them the tools of choice to characterize genomic aberrations for research and diagnostic purposes. For clinical applications, screening the whole genome or exome is challenging owing to the large genomic area to be sequenced, associated costs, complexity of data, and lack of known clinical significance of all genes. Consequently, routine screening involves limited markers with established clinical relevance. This process, referred to as targeted genome sequencing, requires selective enrichment of the genomic areas comprising these markers via one of several primer or probe-based enrichment strategies, followed by sequencing of the enriched genomic areas. Here, the authors review current target enrichment approaches and next generation sequencing platforms, focusing on the underlying principles, capabilities, and limitations of each technology along with validation and implementation for clinical testing.